Pengaruh Pemberian Pakan Fermentasi terhadap Pertumbuhan dan Efisiensi Pakan Sapi Potong - Heriyanto Heriyanto (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The improvement of feed quality through fermentation technology has been widely applied in ruminant production systems to enhance nutrient digestibility and feed efficiency. This study aimed to evaluate the effect of fermented feed on growth performance and feed efficiency in beef cattle. A total of 20 male Bali cattle with an average initial weight of 200 ± 15 kg were used in this experiment, divided into two treatment groups: control (conventional feed) and treatment (fermented feed with local microbes). The research was conducted for 90 days using a randomized complete design. Data collected included daily weight gain, feed intake, and feed conversion ratio (FCR). Results showed that cattle receiving fermented feed exhibited significantly higher average daily gain (0.85 kg/day) compared to the control group (0.65 kg/day) (p < 0.05). Furthermore, the FCR of the treatment group was lower (7.2) compared to the control group (9.1), indicating better feed efficiency. In conclusion, fermented feed can significantly improve growth performance and feed utilization efficiency in beef cattle, providing a practical strategy to optimize productivity in tropical livestock systems.